Agro-climatic Zones of India - Venkateswarlu, J; Ramakrishna, Y S; Rao, A S (Annals of Arid Zone, 2016)
Different methods followed to classify Indian sub-continent into homogeneous agro-climatic zones have been summarized and an attempt made to regroup the 126 agro-climatic zones identified by ICAR under the NARP programme. The present exercise was made to combine contiguous zones, having similar soil, climatic, physiographic and cropping patterns, thereby reducing the total number of zones to a manageable number of 60, in addition to the 2 zones representing Andaman- . Nicobar islands and Lakshadweep islands.